Hypothetical 22-Year Diet Intervention: Adherence to the Dietary Approach to Stop Hypertension (DASH) Diet and Risk of Heart Failure in Swedish Men and Women. (14th June 2022) - Ibsen, Daniel; Chiu, Yu-Han; Gemes, Katalin; Wolk, Alicja
Abstract: Objectives: To use the target trial approach to emulate the effect of sustained adherence to the DASH diet on the 22-year risk of heart failure. Methods: We included men and women aged 45–83 years without previous heart failure, ischemic heart disease, cancer and answered the diet and lifestyle questionnaires in 1997 from the Swedish Mammography Cohort (SMC) and the Cohort of Swedish Men (COSM). In 2008–2009, a follow-up questionnaire was sent to both men and women. For women, pre-baseline dietary intake was assessed in 1987. The parametric g-formula was used to estimate the risk of heart failure under sustained adherence to the DASH diet and no dietary intervention (i.e., the usual dietary intake). Models were adjusted for baseline confounders, confounder histories and, in women only, pre-baseline dietary intake. Adherence to the DASH diet was defined as intake within the ranges of 10 food groups: whole grains, vegetables, fruits, low-fat dairy, red meat, poultry, fish, nuts and legumes, fats and oils, and sweets and added sugar. Incidence of heart failure was ascertained using the Swedish National Patient Register up to 31 December 2019. Death was considered as a competing risk in the g-formula, meaning that we estimated the cumulative cause-specific risk of heart failure. Results: In total, 31, 238 participants were eligible in SMC and 34, 939 in COSM at baseline. Over the follow-up period, 2739 developed heart failure and 4218 died in SMC. The corresponding number were 3862 and 6755 in COSM. The 22-year risk of heart failure was 13.0% for adherence to the DASH diet compared with 15.2% with no intervention (risk difference −2.2%, 95% CI −3.9, −0.7%) in SMC and correspondingly in COSM 14.1% vs. 16.2% (risk difference −2.1%, 95% CI −3.5, −0.7%). The risk ratios were 0.85 (95% CI 0.75, 0.95) in SMC and 0.87 (95% CI 0.78, 0.96) in COSM. Conclusions: Our target trial shows that sustained adherence to the DASH diet may reduce the risk of heart failure compared with usual dietary intake in a middle-aged and elderly Swedish population. Funding Sources: This study was supported by the Swedish Research Council (VR grant 2015-02, 302), and by the Swedish Research Council for Environment, Agricultural Sciences and Spatial Planning (FORMAS grant 2016-00, 308).